Research Advances of Traditional Chinese Medicine in Cancer Immunotherapy - Jing Li; Shengqi Wang; Neng Wang; Zhiyu Wang (Wolters Kluwer Health/LWW, 2020)
Tumorigenesis are closely associated with the immune function of the human body. Immunotherapy has emerged as a novel and promising treatment strategy in multiple malignancies in the 21st century. Traditional Chinese medicine (TCM) has been extensively used for cancer treatment in China and surrounding countries for it exerts efficient therapeutic effects with few side effects. In recent years, studies have demonstrated that TCM plays a unique and reliable role in regulating tumor immunity. TCM can enhance the antitumor immune response function by regulating the secretion of cytokines, reshaping the balance of immune cells, and regulating immune checkpoints to relieve the immunosuppression. In addition, TCM can reduce the side effects (e.g., cytokine storm) of cancer immunotherapy. Based on the current research of active immunotherapy and passive immunotherapy, this review summarizes the potential applications and existing problems of TCM in tumor immunotherapy. This review may be helpful in illuminating the scientific basis of TCM in tumor immunotherapy, promoting its internationalization, as well as shedding innovating new strategies for the development of tumor immunotherapy.